Johannesburg and its epidemics: Can we learn from history? - Harrison, Philip (Gauteng City-Region Observatory, 2020)
Covid-19 has massively disrupted life globally and locally, bringing many uncertainties in its wake. It is not, however, the first epidemic to pummel the Gauteng City-Region. This GCRO Occasional Paper provides a detailed account of previous epidemics, including smallpox, the plague, influenza, measles, polio, scarlet fever and HIV/Aids. It asks whether we can learn from this history to benefit the present time. It shows that although we must use history judiciously because circumstances vary enormously across time, there are persisting themes and a knowledge of history can help direct attention to critical concerns. These themes are addressed in the report and include: the uncertain and idiosyncratic course of epidemics; social fault-lines exposed through epidemics, worsened through scapegoating, stigmatising and pathologising; the effects on livelihoods and the economy; the impacts on spatial form and infrastructures; the ways in which governance impacts the course of epidemics; and the ways in which epidemics influence the continued evolution of governance.
Keywords: epidemics, Johannesburg, history